Acid pasteurized chopped Ilocos white garlic (Allium sativum L.) - Rojas, Abigail Avendano (College of Home Economics, University of the Philippines Diliman, 2012)
The study adapted an acid pasteurization processing method for Ilocos White garlic (Allium sativum L.). Fresh Ilocos White garlic used had cream to yellow color, high firmness reading, near neutral pH and moderately high Aw. Hot air drying at 100⁰C for 15 min utilized as a peeling treatment allowed for easier peel removal while maintaining acceptable % yield, firmness values and color. Chopped garlic was packed in glass jars and acidified with 0.80% tartaric acid solution using a 1:1 garlic to cover liquor ratio to reach a pH 4.0. The calculated D95⁰C-value at pH 4.0 of Bacillus cereus spores was equal to 8.49 min based on the mathematical model by Leguerinel and Mafart (2001) which modeled the pH and organic acid influence on thermal inactivation of B. cereus spores. The P95(theoretical) value was equal to 50.94 min based on a 6D process. Heating at 95⁰C for 15 min resulted in an adequate P95(calculated) value equal to 54.50±0.21 min. Acid-pasteurized Ilocos White garlic had yellowish brown color, pH of 4.36, %TA of 0.81%, <10CFU/g B. cereus count and <1000 CFU/ g YMC. The processed Ilocos White garlic was evaluated to have near strong garlic aroma, near dark yellow color and near soft firmness. Incorporation of the product into garlic fried rice and peanuts with garlic food systems indicated only like slightly consumer rating and near moderate garlic aroma and flavor. Slight perceived sourness of the food models was not significantly different from the control which indicated that sourness perceived was not due to acidification. The addition of another non-thermal hurdle leading to lower heat treatment is recommended to preserve garlic aroma and flavor of the acid-pasteurized garlic.